Two Case Reports of Moderate covid-19 With Chronic Co-Morbidities Treated Through Ayurveda Medicines - Miti Virani (Asian Journal of Pharmaceutical Research and Development, 2025)
COVID-19 or SARS-COV-2 is caused due to the strain of corona virus characterized by respiratory and other systemic illness such as cough, sore throat, breathlessness, fever, tiredness, loss of taste and smell, myalgia, diarrhea, abdominal pain.It is a medical public health emergency declared by WHO in January 2020. As such no specific treatment is available for this disease.Symptomatic and supportive treatment like antiviral, corticosteroids, anticoagulants,vitamin supplements and mechanical ventilation are applied in conventional treatment.Ayurveda science also offers measures the patient to relieve symptoms as well as cure the asymptomatic patient or patient with mild symptoms. The patients who get the severe illness with co-morbidity requires tertiary care from the beginning itself but can also be co-prescribed with Ayurveda medicines in order to reduce the mortality and to buy the more time to have intensive management. The authors reportedtwo moderate cases of COVID-19 having one or more chronic co-morbidities treated successfully with Ayurvedic therapeutic approach. Significant improvements were noticed in the symptoms like fever, breathlessness, cough & lethargy after Ayurvedic treatment was added. Both of the patients got the negative result of SARS-COV-2 by the 10th day of the ayurvedic treatment though both of them had co-morbidities. One had hypertension and cardiac arrhythmia while another one had bronchial asthma.